186 Community Research Academy: Lifting Community Voices for Equity in Health Research and Innovation - Lula Mae Phillips; Jennifer Sarah Tiffany-E; Natasha Ashley-Natasha Ashley; Agnes Chayka (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: To engage community partners in full spectrum of translational sciences participants will: 1. Develop community-based research projects. 2. Evaluate pilot awards submitted to the Community Advisory Board for funding. 3. Actively participate in the research cores at the CTSC METHODS/STUDY POPULATION: The Academy workshop curriculum supports an in-depth examination of the translational research process, introduction to the CTSC Community Advisory Board; as well as to community based participatory research; grant evaluation process, and the need for active community involvement in various cores, and clinical trials. Workshops presented by tenured professionals and community leaders with multi-media out of class assignments. Scheduled sessions were 1 hour, and 15 minutes. Exams given post class session with a mean score of 22.8/30 for session 1 and a mean score of 23.80/30 for session 2. RESULTS/ANTICIPATED RESULTS: The Community Research Academy (CRA) has thus far held for two sessions. Of the 45 enrollees, 20 completed the entire program. Of those, ten have joined the CAB board; and three have actively participated in the pilot award review process. One of the CRA graduates will be publishing her photo novella assignment in Health Affairs. One person changed careers,: and several people have taken all the classes for a second time. Many participants originally came from our faith-based connections. Now word of mouth is expanding the program. DISCUSSION/SIGNIFICANCE: Community engagement ensures that the fresh voices of diverse populations are involved in translational science. Their input ultimately leads to creating novel clinical innovations; such community-driven ingenuity which addresses the deeply felt needs of those communities.